International investment arbitration and the international fight against corruption - Carbajal Valenzuela, Christian (2021)
Within international investment arbitrations, international protection is usually denied to investments that have been made through acts of corruption as the majority of the investment arbitration tribunals do not assume jurisdiction or the claims are considered inadmissible. These decisions, inevitably and indirectly, lead to the exoneration of international responsibility of the defendant States due to the corruption of their public officials, even when these illicit acts are not configured unilaterally, existing, in most cases, shared responsibility between the investor and the State. By not sanctioning corruption, the current crisis in the investment dispute resolution system is aggravated, which, on the contrary, requires urgent and consensual solutions to guarantee a viable reform. Faced with this worrying scenario, this article examines mechanisms to achieve the confluence between International Investment Law, International Anti-Corruption Law and the international standards concerning the Responsibility of States for Internationally Wrongful Acts. We argue that if illicit behavior by public officials is found, depending on the circumstances of each case, the investment arbitration tribunals should rule on the international responsibility of the defendant States for failing to comply with the obligations arising from the International Anti-Corruption and Investment Treaties. Likewise, depending on the case, they must sanction investors and States, since both parties may be responsible for committing the illicit acts of corruption. Recognizing the limitations inherent to the powers of arbitral tribunals, it is possible to affirm that they cannot remain outside the international fight against corruption, as it has been agreed by the international community in the treaties that exist on this matter, being this the situation when the tribunals declare their lack of jurisdiction, avoiding to decide on the acts of corruption identified within the specific case.